Editor’s Foreword - Radaev, Vadim (Journal of Economic Sociology, 2024)
Dear colleagues, We find ourselves at the edge of a new leap year (the seventh leap year for our journal). Normally, people expect something unexpected from it. Let us hope that this year will not bring any new troubles to us.